Optimizing Multilingual Learners’ Potential: An Arabic Pedagogy Model at the Indonesian School of Jeddah in the Era of Industry 4.0 - Fauzi, Maghfur Afnan; Madjid, Muh. Naim (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
Abstract This study examines the learning of Arabic Fusha (MSA) at Indonesian School of Jeddah within a multilingual context, where students use Indonesian, Arabic ‘Amiyah, and English in their daily lives. Despite high exposure to Arabic, students face challenges in vocabulary acquisition and listening skills, raising questions about the effectiveness of conventional teaching methods and the potential of digital media integration. This research employs a qualitative approach through library research, utilizing content analysis of literature related to Arabic Fusha learning, multilingualism, and digital learning tools. Findings indicate that the integration of digital media, supported by family and social environments, can enhance motivation, comprehension, and overall learning effectiveness. The study contributes theoretically to Arabic language pedagogy in a multilingual context within the Industry 4.0 era and offers practical recommendations for developing technology-based learning models tailored to the needs of diaspora students.